Effect of Moisture Content on Mechanical Properties of AAM Natural Fiber-Reinforced Isophthalic Polyester Composites. (28th January 2022) - Ramakrishnan, T.; Senthil Kumar, S.; Samuel Chelladurai, Samson Jerold; Gnanasekaran, S.; Geetha, N. K.; Arthanari, Ramesh; Debtera, Baru
Abstract : Composite fiber reinforcement is one such proficient material that substitutes for useful applications for conventional and polyester blends where little weight and thus less energy conservation is required. This study highlighted the importance of recently discovered Agave Angustifolia marginated (AAM) fibers extracted by a manual process from AAM plants. This paper observes the various properties of the mechanical and moisture intake characteristics of AAM fiber and compares these to other naturally occurring fibers. Using isophthalic polyester resin, the mixed chopped AAM fiber-reinforced composite is prepared and detailed preparation techniques are presented. During physical composite testing, fiber pull-outs on the broken samples were investigated. Additionally, the experimental evidence demonstrates that increasing the volume fraction helps to increase the tensile, bending, and modulus of the AAM fiber composite. The chopped fiber isophthalic polyester reinforcement reaches its improved tensile strength and modulus at a 25% Vf about the 20 mm length of the fiber.